Image stitching of dissimilar images - Licu, Gil Rupert (Animo Repository, 2016)
Image stitching is done by combining multiple input images such that the ideal result is a single image that contains contexts from all the inputs as well as seamless transitions between contexts. It is most commonly used in the field of panoramic photography. Large dissimilarities in the input image set are very problematic in image stitching applications. These cause several objections in the resulting output, such as ghosting and distortion. This paper presents a fully automated image stitching process that is aimed at reducing objections and increasing stitching quality. The proposed implementation adapted existing methods with an objective of having am implementation that is more robust against the dissimilarities caused by perspective, illumination, and occlusion. © 2015 IEEE.